Porphyromonas gingivalis exacerbates experimental autoimmune encephalomyelitis by driving Th1 differentiation via ZAP70/NF-κB signaling - Dai, Dong; Cao, Guoqin; Huang, Shengyuan; Xu, Min; Wang, Jilei; Han, Xue; Ma, Qiuying; Lin, Jiang (Frontiers in Immunology, 2025)
BackgroundMultiple sclerosis (MS) is characterized by chronic inflammation and demyelination within the central nervous system (CNS), primarily driven by the abnormal activation of the peripheral immune system, notably Th1 cells. As the principal pathogen in periodontitis, Porphyromonas gingivalis (P. gingivalis) is linked to an increased risk of multiple sclerosis progression; however, its role in central nervous system inflammation remains unclear. In this study, we aimed to determine whether P. gingivalis promotes peripheral Th1 cell differentiation via the ZAP70/NF-κB signaling pathway, thereby exacerbating experimental autoimmune encephalomyelitis(EAE), a model of multiple sclerosis.MethodsC57BL/6J mice were randomly divided into healthy control, periodontitis, EAE, and periodontitis with EAE group. Neurological function was assessed using Weaver’s score. Histopathology (H&E, LFB staining) and Evans blue dye leakage evaluated inflammation, demyelination, and blood-brain barrier(BBB)permeability. Th1 and Th17 cells were quantified by flow cytometry, while immunofluorescence staining was performed to analyze Claudin-5, IFN-γ +CD4+ T -positive cell and IL-17+CD4+-positive cell expression. Western blotting measured NF-κB and related protein expression. Reference-based mRNA sequencing analysis and Kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment was conducted to identify differential gene expression and pathway enrichment.ResultsIn mice with experimental autoimmune encephalomyelitis, P. gingivalis infection significantly elevated Th1 cell proportions in the peripheral blood, increased interferon-gamma expression, and exacerbated central nervous system inflammation and demyelination by enhancing blood–brain barrier permeability. The infection also activated the ZAP70/NF-κB pathway, essential for peripheral Th1 differentiation, as evidenced by p65 nuclear translocation and significant upregulation of Th1-related genes, including those of the transcription factor Tbx21 and interleukin-12 receptors. In vitro, P. gingivalis lipopolysaccharide (LPS) stimulated Th1 differentiation via ZAP70/NF-κB, which was effectively blocked by pathway inhibitors, reducing Th1 cells and pro-inflammatory factors.DiscussionOur findings elucidate, for the first time, how P. gingivalis infection promotes central nervous system inflammation by driving Th1 cell differentiation via peripheral ZAP70/NF-κB pathway activation. This highlights P. gingivalis as a local periodontitis pathogen and significant contributor to neuroinflammation, providing new insights into the pathogenesis of multiple sclerosis and identifying promising targets for immunomodulatory therapeutic strategies.